A rapid anion-exchange chromatography for measurement of cholesterol concentrations in five lipoprotein classes and estimation of lipoprotein profiles in male volunteers without overt diseases. (November 2015) - Manita, Daisuke; Hirowatari, Yuji; Yoshida, Hiroshi
Background: Analysis of lipoprotein profile gives important clinical information for lipid-lowering therapy which prevents atherosclerotic diseases. The lipoprotein classes can be isolated from serum with ultracentrifugation, which inevitably consumes a long time and needs large serum volume. We have established a method with anion-exchange chromatography with 1.0 µL of the injected volume in 5.2 min for assay of one sample. Methods: One-hundred-forty-one male volunteers without overt diseases were divided three groups (Group 1, non-dyslipidemia with LDL-cholesterol [LDL-C] <120 mg/dL and HDL-cholesterol (HDL-C) ≥40 mg/dL; Group 2, borderline dyslipidemia with 120 ≤ LDL-C < 140 mg/dL and HDL-C ≥40 mg/dL; Group 3, dyslipidemia with LDL-C ≥ 140 mg/dL or HDL-C < 40 mg/dL). Their lipoprotein profiles were evaluated by rapid anion-exchange chromatography, which measured concentrations of HDL-C, LDL-C, IDL-cholesterol, VLDL-cholesterol, and other fraction (chylomicron + lipoprotein [a])-cholesterol (other-C). Results: The within-day and between-day assay coefficients of variation of lipoprotein cholesterol values were 0.33–4.31% and 2.37–9.19%, respectively. The correlation coefficients between values of HDL-C, LDL-C, IDL-C and VLDL-C by the anion-exchange chromatography and those by ultracentrifugal method were 0.97, 0.92, 0.58 and 0.94, respectively. Group 3 had significantly lower HDL-C and higher concentrations of IDL-C, VLDL-C and other-C than did Group 1. Group 2, borderline dyslipidemia, had significantly higher concentrations of IDL-C and VLDL-C than did Group 1. Conclusion: The rapid anion-exchange chromatography assay may be sufficiently applied to the assessment of borderline dyslipidemia.